ChemInform Abstract: Cyclization Cascades Initiated by 1, 6‐Conjugate Addition. Issue 12 (14th March 2013) - Brooks, Joshua L.; Frontier, Alison J.
Abstract The dienyl diketones containing tethered acetates (Ic) and (VII) selectively undergo two different 1, 6‐conjugate addition‐initiated/ cyclization cascades.